2018
DOI: 10.2196/cardio.9424
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Technology Utilization Among Patients From Diverse Cultural and Linguistic Backgrounds Attending Cardiac Rehabilitation in Australia: Descriptive, Case-Matched Comparative Study

Abstract: BackgroundBarriers to attending cardiac rehabilitation (CR), including cultural and linguistic differences, may be addressed by recent technological developments. However, the feasibility of using these approaches in culturally and linguistically diverse patients is yet to be determined.ObjectiveThis study aims to assess the use of mobile technologies and features, as well as confidence in utilization across patients speaking different languages at home (ie, English, Mandarin Chinese, and a language other than… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Firstly, the results, contrasting with previous studies by [ 14 , 18 , 19 ], suggest that people from CALD backgrounds have similar access, readiness and willingness to engage in telerehabilitation as compared to people from non-CALD backgrounds. In support of our findings, there has been one study by Zhang and colleagues (2018) [ 32 ], who evaluated the technology use between people from CALD and non-CALD groups and found that even though usage pattern of technologies may be different, the level of access to technology was comparable between CALD and non-CALD groups. This raises the question as to why previous studies have found that people from CALD group were less likely to use telerehabilitation.…”
Section: Discussionsupporting
confidence: 87%
“…Firstly, the results, contrasting with previous studies by [ 14 , 18 , 19 ], suggest that people from CALD backgrounds have similar access, readiness and willingness to engage in telerehabilitation as compared to people from non-CALD backgrounds. In support of our findings, there has been one study by Zhang and colleagues (2018) [ 32 ], who evaluated the technology use between people from CALD and non-CALD groups and found that even though usage pattern of technologies may be different, the level of access to technology was comparable between CALD and non-CALD groups. This raises the question as to why previous studies have found that people from CALD group were less likely to use telerehabilitation.…”
Section: Discussionsupporting
confidence: 87%
“…Finally, logistic regression was employed to determine the factors influencing hospital choice by different types of patients. This approach is commonly used [37,38] to predict a categorical (mainly dichotomous) variable with a mix of continuous and categorical predictor variables [37,39]. The regression model here predicts the probability of admission as a public patient whilst holding PHI cover.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies are likely to explore language barriers, which is one of the most important challenges for CALD people. A limitation of defining CALD by LSAH is that it might be affected by acculturation [ 58 ]. Specifically, children of immigrants (from CALD backgrounds) living in Australia for many years might report English as LSAH [ 52 ]; therefore, they would be misclassified as the non-CALD group.…”
Section: Discussionmentioning
confidence: 99%